Development And Grain Quality Of Soybean Cultivars Treated With Pyraclostrobin And Biostimulant - Machado, Fellipe Goulart; Menezes, Carlos César Evangelista; Campos, Gabriela Wilk Baião; Takano, Hudson Kagueyama; Oliveira Jr, Rubem Silvério de; Braz, Guilherme Braga Pereira (Comunicata Scientiae, 2018)
Products with physiological effects on plants to optimize agricultural production is increasingly used; they can change the development of plants and the chemical characteristics of seeds. The objective of this work was to evaluate the development of soybean cultivars and the protein and oil contents of soybean grains after treatment with pyraclostrobin and biostimulant. The experiment was carried out with soybean crops without irrigation. The experimental design was a randomized complete block design, with five replications, using a 3 × 3 factorial arrangement consisting of three cultivars of different maturation times (very early, M6952IPRO; early M7739IPRO; and medium, ST797IPRO), and three treatments with products that cause physiological effects (control, pyraclostrobin, and control + biostimulant). The pod, leaf, and stem dry weights, number of pods, 100-grain weight, grain yield, and oil and protein contents of the soybean plants were evaluated. The data were subjected to analysis of variance, and Tukey’s test at 5% probability. The effects of the products used (pyraclostrobin and biostimulant) vary according to the cultivar and may increase the soybean leaf and pod dry weights, and grain protein contents.